Design and characterization of Amoitone B-loaded nanostructured lipid carriers for controlled drug release. (November 2013) - Luan, Jingjing; Zhang, Dianrui; Hao, Leilei; Li, Caiyun; Qi, Lisi; Guo, Hejian; Liu, Xinquan; Zhang, Qiang
Abstract Amoitone B, a novel compound chemically synthesized as the analogue of cytosporone B, has been proved to own superior affinity with Nur77 than its parent compound and exhibit notable anticancer activity. However, its application is seriously restricted due to the water-insolubility and short biological half-time. The aim of this study was to construct an effective delivery system for Amoitone B to realize sustained release, thus prolong drug circulation time in body and improve the bioavailability. Nanostructured lipid carriers (NLC) act as a new type of colloidal drug delivery system, which offer the advantages of improved drug loading and sustained release. Amoitone B-loaded NLC (AmB-NLC) containing glyceryl monostearate (GMS) and various amounts of medium chain triglycerides (MCT) were successfully prepared by emulsion-evaporation and low temperature-solidification technology with a particle size of about 200 nm and a zeta potential value of about −20 mV. The results of X-ray diffraction and DSC analysis showed amorphous crystalline state of Amoitone B in NLC. Furthermore, the drug entrapment efficacy (EE) was improved compared with solid lipid nanoparticles (SLN). The EE range was from 71.1% to 84.7%, enhanced with the increase of liquid lipid. In vitro drug release studies revealed biphasic drug release patterns with burst release initially and prolonged release afterwards and the release was accelerated with augment of liquid lipid. These results demonstrated that AmB-NLC could be a promising delivery system to control drug release and improve loading capacity, thus prolong drug action time in body and enhance the bioavailability.